Empathy and Healing : Essays in Medical and Narrative Anthropology. - Skultans, Vieda (Berghahn Books, Inc., 2008)
For more than three decades the author has been concerned with issues to do with emotion, suffering and healing. This volume presents ethnographic studies of South Wales, Maharashtra and post-Soviet Latvia connected by a theoretical interest in healing, emotion and subjectivity. Exploring the uses of narrative in the shaping of memory, autobiography and illness and its connections with the master narratives of history and culture, it focuses on the post-Soviet clinic as an arena in which the contradictions of a liberal economy are translated into a medical language.